"Teacher, ¿Puedo Hablar en Español?" A Reflection on Plurilingualism and Translanguaging Practices in EFL - Yecid Ortega (Universidad Nacional de Colombia, 2019)
This article uses a classroom experience to exemplify ways in which students as social beings learn English as a foreign language in Colombia and how the teacher uses trans[cultura]linguación. This is a process of making meaning during English-learning tasks while comparing specific linguistic variations as students learn about both their own culture and other people's cultures. Borrowing from plurilingualism and translanguaging, I describe how a teacher attempts to use a social-justice approach to teaching English by valuing her students' linguistic and cultural repertoires. I conclude by outlining the implications this has for proposing a paradigm shift from monolithic frameworks of learning language(s) to more dynamic ones in which students' cultural and linguistic backgrounds are deployed as a platform for addressing issues that are relevant to their communities.